Wybrane problemy ochrony danych dotyczących zdrowia pacjenta w kontekście ustawy o prawach pacjenta i Rzeczniku Praw Pacjenta oraz RODO - Rzucidło, Jakub; Węgrzyn, Justyna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
In the article authors are challenging Regulation (EU) 2016/679 of the European Parliament and of the Council of 27 April 2016 on the protection of natural persons with regard to the processing of personal data and on the free movement of such data, and repealing Directive 95/46/EC (General Data Protection Regulation) with the domestic, polish regulations. They are focusing on the right to medical records and the doctor-patient confidentiality. The analysys has shown that the domestic regulations need to be changed, due to high standards of GDPR.
Keywords: GDPR; General Data Protection Regulation; right to medical records